Beauty is only skin deep: An examination of physical attractiveness, attractive personality, and personal grooming on criminal justice outcomes - Knox, Krysta N.; TenEyck, Michael F. (PloS one, 2023)
Research has found that physical attractiveness is related to a host of benefits across life outcomes. Within the field of criminal justice, physical attractiveness appears to afford individuals leniency at various decision points. This research, however, often fails to include measures of personal presentation beyond simply measuring physical attractiveness. The current study extends this line of research by investigating how physical attractiveness, personality attractiveness, and grooming are related to criminal justice processing decisions. Results from negative binomial and logistic regression analyses indicate that when assessed alone, physical attractiveness significantly decreased the odds of criminal behavior by 18 percent, arrest by 11 percent, conviction by 14 percent, and incarceration by 28 percent—controlling for race, age, and gender. When controlling for personality and grooming, however, physical attractiveness results in a 47 to 53 percent increase in the risk of experiencing these outcomes while having an attractive personality and being well-groomed significantly reduced such risk. These results highlight the importance of considering other factors of appearance and personal presentation when considering how attractiveness influences criminal justice outcomes.